2005
DOI: 10.1143/jjap.44.l1494
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity InSb Hall Effect Biosensor Platform for DNA Detection and Biomolecular Recognition Using Functionalized Magnetic Nanobeads

Abstract: A compact, high sensitivity and low cost biosensing platform based on InSb thin film micro-Hall effect biosensors [30 ×30 µm2; magnetic field sensitivity of 1.8 nT/(Hz)1/2] was developed and used for the detection of DNA molecules labeled with magnetic beads. Magnetic beads (∼200 nm diameter) were functionalized and selectively immobilized onto Hall biosensor surfaces via highly specific hybridization of complementary oligonucleotides and subsequently detected by magnetic susceptibility measurements. The poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Improved devices with a higher magnetic field sensitivity were reported in Ref. [162] in which an array of such Hall crosses indicated the feasibility for multiplexed detection, while a 30 9 30 lm InSb sensor successfully detected 200 nm diameter particles. A recent comparative study on different materials suitable for Hall biosensors [145] concluded that sensors based on semiconductor heterojunctions, such as InAs-AlGaSb, show the highest sensitivity, particularly for the case that beads can be localised to the edges of the device which permits quantitative bead detection [83].…”
Section: Hall Effect Biosensorsmentioning
confidence: 99%
“…Improved devices with a higher magnetic field sensitivity were reported in Ref. [162] in which an array of such Hall crosses indicated the feasibility for multiplexed detection, while a 30 9 30 lm InSb sensor successfully detected 200 nm diameter particles. A recent comparative study on different materials suitable for Hall biosensors [145] concluded that sensors based on semiconductor heterojunctions, such as InAs-AlGaSb, show the highest sensitivity, particularly for the case that beads can be localised to the edges of the device which permits quantitative bead detection [83].…”
Section: Hall Effect Biosensorsmentioning
confidence: 99%
“…This time the sensitivity of the sensor was not investigated as this issue was resolved earlier (Togawa et al, 2005). Manipulation of the beads can be very important for the last steps of the whole analytical scheme shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here we aim to optimize the Hall effect micro-biosensor platform without compromising the ultra-high sensitivity accomplished earlier (Togawa et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]8,9 While bead dimensions and momenta are reduced, signals generated by inductive couplings, foreign ferromagnetic materials in the vicinity of the device as well as low frequency, 1 / f, noise might mask true bead signals. Variations in the ac Hall voltage in response to a step-wise dc field are generally accepted as evidence of the bead presence.…”
Section: Introductionmentioning
confidence: 99%